A TRICHOBEZOAR DIAGNOSED BY ULTRASOUND - Idrees, Mohammad; Afridi, Shah Jehan (Journal of Ayub Medical College Abbottabad, 1996)
Trichobezoar is rare and its diagnosis by ultrasound even rarer It results from eating hair, a type of pica, usually found in irresolute women below thirty. Traditionally its diagnosis has been made on barium meal examination. The case under review clinically presented as a big epigastric mass for which ultrasound was advised. Trichobezoar produces a very characteristic and diagnostic appearance on ultrasound and must be considered in the diagnostic workup of such a condition.